Neurological sequelae of cancer immunotherapies and targeted therapies - Wick, Wolfgang; Berberich, Anne; Platten, Michael (The lancet. Oncology, 2016)
Summary Neurological complications of cancer and of anticancer treatments can be substantially disabling to patients, especially with classic chemotherapies. As a rare but important complication, targeted therapies might also result in similar unwanted effects, partly because inhibition of VEGF is a common downstream effect. Therapeutic antibodies, such as the CD20-depleting antibody rituximab, and underlying haematological malignancies, can induce long-lasting cellular immunosuppression, predisposing patients to opportunistic CNS infections, such as progressive multifocal leukoencephalopathy, where treatment-induced recovery can result in severe reconstitution of immune inflammatory syndromes of the central nervous system. Immune-related neurological adverse events, particularly from immune-activating checkpoint inhibitors, occur as a result of immune activation, resulting in organ-specific autoimmune-like disease. The prevalence of immune-related neurological adverse events might only be about 1%—a low prevalence compared with toxicities in other organs—but it constitutes new patterns of neurological toxic forms, which could result in considerable morbidity and fatal outcomes. Clinicians should be aware of treatment-associated neurotoxicity, and consider discontinuation of the drug with parallel supportive measures to help patients.